Realisation of Constituents in English and Kurdish - Dilovan Sayfuddin Saady; Hatam Wlya Muhamad (Zanco Journal of Humanity Sciences)
This study entitled "Realisation of constituents in English and Kurdish languages"  focuses on the definitions of constituent then on some ways by which they are realized. It shows the words that form constituents  . It indicates that one word or more can be a constituent. The problem here is that learners are unable to realise constituent and its type in a sentence .This is due to their lack of knowledge about phrases and their functions .So a constituent can be defined as some word plus all the words depending on it, either directly or indirectly .In other words, that word plus all the dependency chains lead up to it. These constituents have various functions hinging upon the positions they occur in sentences. Here ,the immediate and ultimate constituents are dealt with too. The aim    of this study is not to show the functions but would rather show the tests that make readers be sure that a part is a constituent. These tests may or may not vary in each language. In Kurdish language mainly,the types of constituent (immediate ,intermediate and ultimate) are dealt with too. In this study, the tests that are indicated for establishing constituent are shown in both English and Kurdish languages. The most widely used tests for constituents in syntax are : topicalization, proform substitution ,  fragments , clefting , vp-ellipsis ,pseudo clefting .The significance of the research lies in the fact that different other topics are dealt with for dealing with this subject.  Readers or learners can benefit from them ,for example, types of constituents ,proform, clefting ,….in case their researches are about one of these topics. Finally,It is concluded that for a part to be a constituent, it should not meet all the tests or conditions of constituents. But if it meets one or two condition(s)or tests, it would be considered a constituent. In English there are many tests that assure us that a part is a constituent but in Kurdish there are not many tests for this purpose. In both languages ,the same types of constituents ;immediate ,intermediate and the ultimate are realized and identified.